Lethality by pneumonia and factors associated to death - Sidnei Ferreira; Clemax C. Sant'Anna; Maria de Fátima B.P. March; Marilene Augusta R.C. Santos; Antonio Jose Ledo A. Cunha (Elsevier, 2014)
Objective: to describe the case-fatality rate (CFR) and risk factors of death in children with community-acquired acute pneumonia (CAP) in a pediatric university hospital. Method: a longitudinal study was developed with prospective data collected from 1996 to 2011. Patients aged 1 month to 12 years were included in the study. Those who left the hospital against medical orders and those transferred to ICU or other units were excluded. Demographic and clinical-etiological characteristics and the initial treatment were studied. Variables associated to death were determined by bivariate and multivariate analysis using logistic regression. Results: a total of 871 patients were selected, of whom 11 were excluded; thus 860 children were included in the study. There were 26 deaths, with a CFR of 3%; in 58.7% of these, penicillin G was the initial treatment. Pneumococcus was the most common pathogen (50.4%). From 1996 to 2000, there were 24 deaths (93%), with a CFR of 5.8% (24/413). From 2001 to 2011, the age group of hospitalized patients was older (p = 0.03), and the number of deaths (p = 0.02) and the percentage of disease severity were lower (p = 0.06). Only disease severity remained associated to death in the multivariate analysis (OR = 3.2; 95%CI: 1.2-8.9; p = 0.02). Conclusion: when the 1996-2000 and 2001-2011 periods were compared, a significant reduction in CFR was observed in the latter, as well as a change in the clinical profile of the pediatric inpatients at the institute. These findings may be related to the improvement in the socio-economical status of the population. Penicillin use did not influence CFR. Resumo: Objetivo: descrever a taxa de letalidade (TL) e os fatores de risco de óbito em crianças com pneumonia grave adquirida na comunidade (CAP) em um hospital universitário pediátrico. Método: foi desenvolvido um estudo longitudinal com dados prospectivos coletados de 1996 a 2011. Foram incluídos no estudo pacientes com idade entre 1 mês e 12 anos de idade. Foram excluídos aqueles que deixaram o hospital desconsiderando as recomendações médicas e aqueles transferidos para UTI ou outras unidades. Foram estudadas as características demográficas, clínicas e etiológicas e o tratamento inicial. As variáveis associadas a óbito foram determinadas por análise bivariada e multivariada utilizando regressão logística. Resultados: foi selecionado um total de 871 pacientes, dos quais 11 foram excluídos; assim, foram incluídas no estudo 860 crianças. Houve 26 óbitos, com uma TL de 3%; em 58,7% desses, penicilina G foi o tratamento inicial. Pneumococo foi o patógeno mais comum (50,4%). De 1996 a 2000, houve 24 óbitos (93%), com uma TL de 5,8% (24/413). De 2001 a 2011, a faixa etária de pacientes internados foi mais velha (p = 0,03) e o número de óbitos (p = 0,02) e o percentual de gravidade das doenças foram menores (p = 0,06). Apenas a gravidade das doenças continuou associada a óbito na análise multivariada (RC = 3,2; IC de 95%: 1,2-8,9; p = 0,02). Conclusão: quando os períodos de 1996-2000 e 2001-2011 foram comparados, foi observada uma redução significativa na TL no último período, bem como uma alteração no perfil clínico dos pacientes hospitalizados no instituto. Esses achados podem estar relacionados à melhora na situação socioeconômica da população. O uso de penicilina não influenciou a TL. Keywords: Pneumococcal pneumonia, Penicillin G, Case-fatality rate, Inpatients, Pediatric hospitals, Palavras-chave: Pneumonia pneumocócica, Penicilina G, Letalidade, Pacientes internados, Hospitais pediátricos